Pengungkapan CSR, Intensitas Modal, Leverage Pada Agresivitas Pajak - Suryaningtyas; Purwanthari Sawitri, Aristha (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2024)
The study aims to understand the impact of corporate social responsibility, capital intensity using asset intensity, leverage using Debt To Asset Ratio (DAR) and tax aggressiveness using Effective Tax Rate (ETR). There were 9 company samples during the five-year study using a method to take samples using the purposive sampling method. The analysis method uses multiple regression analysis assisted by SPSS software for windows version 22.0. The results of the study partially showed the influence of corporate social responsibility variables on tax aggressiveness, capital intensity variables affecting tax aggressiveness, and leverage variables affecting tax aggressiveness. The results of the study simultaneously showed that corporate social responsibility, capital intensity, and leverage together affect tax aggressiveness. The results of the study provide an understanding that corporate social responsibility, capital intensity, and leverage can be utilized by companies to avoid tax aggressiveness.